Solving economic dispatch and unit commitment problem in smart grid system using eagle strategy based crow search algorithm - Rachid HABACHI; Achraf Touil; Abdellah Boulal; Abdelkabir Charkaoui; Abdelwahed Echchatbi (Institute of Advanced Engineering and Science, 2019)
The economic dispatch problem of power plays a very important role in the exploitation of electro-energy systems to judiciously distribute power generated by all plants. The Unit commitment problem (UCP) is mainly finding the minimum cost schedule to a set of generators by turning each one either on or off over a given time horizon to meet the demand load and satisfy different operational constraints. This research article integrates the crow search algorithm as a local optimizer of Eagle strategy to solve economic dispatch and unit commitment problem in smart grid system.